The contribution of the instrumented Timed-Up-and-Go test to detect falls and fear of falling in people with multiple sclerosis - Hershkovitz, Leora; Malcay, Ofir; Grinberg, Yevgenia; Berkowitz, Shani; Kalron, Alon (Multiple sclerosis and related disorders, 2019)
•The study provides new insights into the Timed-Up-and-Go test in the MS population.•The sit-to-stand transition is related to fear of falling in people with MS.•Subcomponent scores do not differentiate between MS fallers and non-fallers.•Cognitive-motor interference in the Timed-Up-and-Go test is not unique in MS. Fear of falling (FoF) and actual falling typifies two common complaints in people with MS (PwMS). The objective of our study was to examine the Instrumented Timed-Up-and-Go test (ITUG) in relation to falls and FoF in PwMS. This case-control study comprised 75 participants; 50 PwMS (33 women), aged 44.2 (S.D = 7.2) and 25 healthy subjects (18 women) aged 44.4 (S.D = 8.6). The ITUG test was evaluated by the APDM Mobility lab (Portland, OR, USA) and was completed under two task conditions, normal and while performing a cognitive test (ITUG-cog). FoF was evaluated by the FES-I questionnaire. PwMS were divided into subgroups of fallers and non-fallers based on their fall history. Total duration to complete the ITUG and ITUG-cog was higher in the PwMS group compared to the healthy controls. Total duration to complete the ITUG-cog was higher compared to the normal ITUG in both groups. However, non-significant differences were found for the condition x group factor. The total duration to complete the ITUG was increased in the MS fallers compared to the non-fallers. No other differences in ITUG measures were found between MS subgroups. According to the regression analysis, the sit-to-stand phase explained 22.7% of the variance relating to FoF in PwMS (R2 = 0.227). The study provides new insights into the TUG test in PwMS. The sit-to-stand transition appears to be a major component associated with FoF. Furthermore, the cognitive-motor interference in conjunction with the ITUG is probably not unique in PwMS.